Resolution on the public lands (House doc. (North Carolina. General Assembly. House of Commons), 1852)
1852 House Resolution requesting that the United States Senators and Representatives from North Carolina seek a fair portion of the appropriations from public lands, to be applied to the state's internal improvements, and other needs.